Exploring Gender Differences in Mathematical Creativity: Linking Problem Posing and Problem Solving - Ulusoy, Fadime; Sadak, Musa; Incikabi, Lutfi; Pektas, Murat (Wiley, 2025)
ABSTRACTThis study explores gender‐based differences in sixth‐grade students' potential for mathematical creativity through the interrelated processes of problem solving (PS) and problem posing (PP), grounded in a multidimensional framework of creativity—encompassing fluency, flexibility, and originality. A total of 346 sixth graders from public schools in a northern coastal city of Turkey participated. They completed validated PP and PS tasks, and their responses were scored using established creativity metrics, which served as indicators of the potential for creative mathematical thinking. Multiple linear regression analyses were conducted to examine the predictive relationships between the creativity dimensions across domains, with gender included as an interacting factor in the models. The results revealed that female students significantly outperformed male students in their overall PP and PS creativity scores. Moreover, regression analyses indicated that fluency and originality were significant predictors of creativity across domains, while flexibility did not emerge as a significant predictor. Notably, for female students, PS fluency predicted PP performance, whereas PP originality predicted PS outcomes. For male students, the predictive effect of PS fluency on PP was found to be stronger, and originality in PP also predicted CPS. These findings emphasize the importance of adopting a multidimensional and gender‐sensitive framework when evaluating the potential for creative thinking in mathematics education, and suggest instructional implications for supporting creativity across genders.